Experiences on electronic supply chain management of electronic companies in Vietnam: The roles of information sharing components - Nguyễn Thị Đức Nguyên (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2021)
In the context of many businesses in the electronic supply chain are facing opportunities and challenges when participating in the global supply chain, the question is whether to take advantage of the information sharing flow in the supply chain as well as effective information management can contribute to improve supply chain management performance. This study focuses on the practical experiences of supply chain management of two typical electronic enterprises in Vietnam in order to identify the key components of information sharing in electronic supply chains. The findings identify four key components of information sharing that affect the efficiency of electronic supply chain of electronic companies in Vietnam, including information sharing with suppliers, information sharing with customers, cross-functional information sharing and intra-organizational knowledge sharing. Accordingly, close cooperation among supply chain partners helps to share information regularly and has a high information quality, and business managers play a very important role in promoting effective information sharing in the supply chain. Overall, this study serves as a helpful reference for managers to have appropriately strategic plans for improving information flow in the supply chain and the supply chain efficiency of manufacturing companies in general, especially electronic supply chain in Vietnam.